Anthropogenic and climatic‐driven peatland degradation during the past 150 years in the Greater Khingan Mountains, NE China. (8th October 2021) - Han, Dongxue; Gao, Chuanyu; Liu, Hanxiang; Li, Yunhui; Cong, Jinxin; Yu, Xiaofei; Wang, Guoping
Abstract: Relationships between modern pollen, climate, and human activities are important for improving the explanation of fossil records. To better understand anthropogenic and climatic impact on peatland vegetation and environment, we assessed the impact of the human influence index (HII) on modern pollen assemblages from 61 surface soil samples (different land‐use types) in the Greater Khingan Mountains by using detrended correspondence analysis and redundancy analysis. Based on the palynological analysis, 210 Pb age‐depth model, and weighted averaging partial least squares, we reconstructed HII values of Tuqiang peatland in the Greater Khingan Mountains during the last 150 years. The reconstructed HII values demonstrated that the intensity of human activities increased gradually before 1900 AD, when the population of Heilongjiang Province was less and its native inhabitants continued to hunt and gather. During the period of 1900–1950 AD, human influence intensity increased sharply and reached peak values. Wars and placer gold mining caused large numbers of people immigrated north to Heilongjiang Province, rapid population growth strengthened the human impact intensity. In addition, invaders exploited the forest resources without limit. Widescale deforestation and land reclamation destroyed vegetation landscape and reduced forest coverage seriously, which led to soil erosion and land degradation. With the foundation of new China (1949 AD), the implementation of forest protection policies clearly reduced the human disturbance intensity. However, due to the needs of economic development, human influence intensity increased again after 2000 AD.